Stigma among doctors towards people with mental illness - Sharma, Bishnu; Sampath, Harshavardhan; Soohinda, Geeta; Dutta, Sanjiba (International Journal of Research in Medical Sciences, 2018)
Background: Stigma towards adults with mental illness is a longstanding and widespread phenomenon. Stigmatizing attitudes are prevalent not only among the general population but also among doctors. Negative stereotyping of people with mental illness (PMI) leads to prejudice and discrimination, affecting all aspects of their medical care and well-being. The present study attempted to explore stigmatizing attitudes among doctors towards PMI. Methods: The research was observational and cross-sectional in design carried out on doctors in a medical college. Socio-demographic data including field of specialization, experience, and academic post were recorded. The community attitudes towards mental illness (CAMI) and social distance scale were administered. Social desirability bias was corrected for by using the Marlowe-Crowne social desirability scale. Results: Around 54 doctors from the specializations of medicine (n=24), surgery (n=19), and non-clinical fields (n=11) participated. We found no significant differences in attitudes towards mentally ill and social distance between medical specializations (p-values >0.05) even after adjusting for the effects of social desirability bias. Years of specialization experience (p=0.037) and having a family member or close friend with mental illness (p=0.012) were significantly associated with higher scores in the community mental health ideology sub-scale of CAMI. Higher social restrictiveness (p=0.014) and lower community mental health ideology (p=0.008) were associated with greater social distance from PMI. Conclusions: Doctors are not immune to biases and stigmatizing attitudes towards PMI. These attitudes are present across all fields of medical specialization and must be addressed by mental health professionals to ensure optimal care of this vulnerable population.